The Effects of Policy Funds on the Investment and Management Stabilization Financing of Small- and Medium-sized Enterprises - Jinhwa Chung; Bohyun Kim; Seongman Moon (East Asian Economic Review (EAER), 2023)
This study empirically examines the impacts of policy funds from three different aspects using data on Daegu City's local government loans. First, we estimate the influence of policy funds on mitigating financial constraints affecting the investment decisions of Small- and Medium-sized Enterprises (SMEs), yielding inconclusive results indicating no significant discernible effects of policy funds. Second, we scrutinize the ramifications of policy funds on enterprise's management stability, revealing that these funds contribute to stabilizing the operations of small-scale enterprises. Third, we explore whether policy funds engender an unintended consequence of bolstering distressed enterprises, presenting empirical evidence that suggests a delayed exit of such enterprises.
Keywords: G20; G30; 330; Policy Funds; SMEs; Investment; Management Stability